Effects of climate change on different geographical populations of the cotton bollworm Helicoverpa armigera (Lepidoptera, Noctuidae) - Huang, Jian (Ecology and evolution, 2021)
The effects of climate change on pest phenology and population size are highly variable. Understanding the impacts of localized climate change on pest distribution and phenology is helpful for improving integrated pest management strategies. Here, the population dynamics of cotton bollworms (Helicoverpa armigera) from Maigaiti County, south Xinjiang, and Shawan County, north Xinjiang, China, were analyzed using a 29‐year dataset at lower latitudes and a 23‐year dataset at higher latitudes to determine the effects of climate change on the population dynamics of H. armigera. The results showed that all generations of H. armigera at both sites showed increasing trends in population size with climate warming. Abrupt changes in phenology and population number occurred after abrupt temperature changes. Climate change had a greater effect on the phenology of H. armigera at higher latitudes than at lower latitudes and led to a greater increase in population size at lower latitudes than at higher latitudes; the temperature increase at higher latitudes will cause a greater increase in the adult moth population size in the future compared to that at lower latitudes; and abrupt changes in the phenology, temperature increase, and population size at lower latitudes occurred earlier than those at higher latitudes. Thus, it is necessary to develop sustainable management strategies for Helicoverpa armigera at an early stage. Climate change had a greater effect on phenology of Helicoverpa armigera at higher latitude than that at lower latitude; climate change caused a more increase of population size at lower latitude than that at higher latitude; the accumulated temperature (AT) percentage at higher latitude had a rapid increase and cause adult moth increase in the future than those at lower latitude; the abrupt changes of phenology, AT and population size at lower latitude were earlier than those at higher latitude. Thus, it is necessary to early make relative strategies to manage the insect pest.